Representations of rural primary school in Brazil (Sao Paulo, 1933-1943) - Souza, Rosa Fatima [UNESP] (Queens Univ, Fac Education, 2016)
This text consists of a study on representations of rural primary schools in Brazil, especially of the state of Sao Paulo, in seeking to understand how the images contributed to strengthen the contempt towards rural school and society. The documentary corpus research consists of 199 photographs of rural schools attached to the reports of the Regional Offices of Education, technical inspection bodies of the Department of Education of the State of Sao Paulo, produced from 1933 to 1943. The photograph analysis focuses on three thematic groups: school building facades, students' and teachers' pictures, and school practices.
Keywords: history of education; rural primary education; rural education in Brazil; elementary school; school culture; Brazil